Analisis Kapasitas Pemerintahan Desa sebagai Pelaku Pembangunan Desa di Desa Oelomin, Kecamatan Nekamese, Kabupaten Kupang - Seger, Marini Sari Dewi (Universitas Syiah Kuala, 2025)
This study aims to describe the governance capacity of Oelomin Village as a development actor, focusing on both individual capacity and organizational capacity within the village government. The research involved 12 informants, utilizing data collection methods such as interviews, observations, and documentation. The collected data were analyzed using a qualitative descriptive approach. The findings indicate that the individual capacity of Oelomin Village government remains low. This is evident in the low level of education, as many officials have not pursued formal education. Additionally, no training programs have been provided for the village government apparatus. Communication within the government, as well as between the village government and the Village Consultative Body (BPD), is not yet fully effective. Collaboration in carrying out tasks and functions is also not optimal, both within the government and in cooperation between the government and the BPD. The organizational capacity of Oelomin Village government is also weak due to the low individual capacity. Although the village government structure follows the regulations set by the Kupang Regency Regional Regulation, it lacks clear task distribution for each division. The utilization of village assets to increase revenue has not been effectively implemented. Furthermore, the government's ability to establish partnerships with external parties remains limited. While some cooperation with NGOs has been established, most of the programs focus on non-physical development, such as educational outreach. The low individual and organizational capacity have resulted in suboptimal village development, preventing the community from fully benefiting from development initiatives.